2007
DOI: 10.1073/pnas.0710183104
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection at the protein network periphery: Evaluation in terms of structural constraints and cellular context

Abstract: Because of recent advances in genotyping and sequencing, human genetic variation and adaptive evolution in the primate lineage have become major research foci. Here, we examine the relationship between genetic signatures of adaptive evolution and network topology. We find a striking tendency of proteins that have been under positive selection (as compared with the chimpanzee) to be located at the periphery of the interaction network. Our results are based on the analysis of two types of genome evolution, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
128
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 46 publications
20
128
1
1
Order By: Relevance
“…Components on the periphery of such networks, like receptors, that interact with a defined set of adapting pathogen molecules can adapt more precisely than those located more centrally and with multiple functions (45,102). Cellular protein networks of the probability of positive selection indicate receptors are topologically more predisposed to this adaptive force than mediators, as are sites on the protein surface than those located internally; as a result, the surface area of the protein selectively constrained could increase as number of interacting partners rises (44). Therefore, the evolutionary patterns at cytokines could be restricted by their functions in binding to many receptor types, including those from beyond the immune system (103), where cytokines play a role in many biological processes.…”
Section: The Causes Of the Contrast Between Gene Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Components on the periphery of such networks, like receptors, that interact with a defined set of adapting pathogen molecules can adapt more precisely than those located more centrally and with multiple functions (45,102). Cellular protein networks of the probability of positive selection indicate receptors are topologically more predisposed to this adaptive force than mediators, as are sites on the protein surface than those located internally; as a result, the surface area of the protein selectively constrained could increase as number of interacting partners rises (44). Therefore, the evolutionary patterns at cytokines could be restricted by their functions in binding to many receptor types, including those from beyond the immune system (103), where cytokines play a role in many biological processes.…”
Section: The Causes Of the Contrast Between Gene Classesmentioning
confidence: 99%
“…Genes whose products interact directly with the environment are more likely to have undergone adaptive change than those that mediate the immune response (44,45). Thus, PAMP recognition receptors like TLRs are good candidates for detecting selection at the population level; previous studies have shown that the avian TLR genes have been subject to selection (46,47).…”
mentioning
confidence: 99%
“…There are always exceptions, because life is a contingent, highly stochastic evolutionary phenomenon, but generally there is reason to think that the coding regions of early developmental or hub genes evolve relatively slowly (Kim et al 2007;H. A. Lawson, unpublished results).…”
Section: Evolutionary Underpinningsmentioning
confidence: 99%
“…The networks of protein-protein interactions, or interactomes (6)(7)(8)(9), although distinctive to their individual organisms, manifest global and local characteristics that are shared across species (10,11). Most notably, the organization of these networks exhibits a scale-free topology (10,12) with a substantial number of highly connected hub proteins (13).…”
mentioning
confidence: 99%